High-Performance Reconfigurable Computing. - Buell, Duncan; El-Ghazawi, Tarek; Gaj, Kris; Kindratenko, Volodymyr (Computer (00189162), 2007)
The article discusses high-performance reconfigurable computers (HPRCs) and their potential. HRPCs are computing systems with multiple microprocessors and multiple field-programmable gate arrays (FPGAs). The FPGAs are used to execute a small portion of the application that takes the most amount of time to perform. The authors feel that these computers have shown exponential improvement over traditional high-performance computers in aspects like performance, power, size, and cost. Some of the latest progress is presented along with some of the problems associated with the technology.